Anti-history : theorizing the past, history, and historiography in management and organization studies - Durepos, Gabrielle; Mills, Albert J., 1945- (Emerald Publishing Limited : Information Age Publishing, 2012)
This book sets out to answer the call for the historic turn in organization studies through the development of an alternative methodology for history, one that we call ANTi-History. In responding to that call, this book contributes generally to the broad critique of the ahistorical nature of management and organization theory, but more specifically it sets out to address the need for more historicized research and in particular, alternative ways of writing and conceptualizing history. The application and theoretical development of ANTi-History is explored through the performance of a series of histories of Pan American Airways.